Ice composition evidence of marine ice transfer along the bottom of a small Antarctic ice shelf - SOUCHEZ R; MENEGHEL M; TISON J. L; LORRAIN R; RONVEAUX D; LOZEJ A; TABACCO I; JOUZEL J.; BARONI, CARLO (1991)
The existence of marine ice transfer along the underside of the Hell's Gate Ice Shelf (Victoria Land), is indicated by an isotopic and chemical study of ice cores. Because of top surface ablation, the marine ice formed at the ice shelfocean interface, ultimately appears at shelf surface. A succession of congelation, platelet and frazil ice is shown to occur. The combined study of stable isotope composition and of the sodium content of these different ice types proves to be a valuable tool for specifying the ice shelf-ocean interactions in this area. Two different freezing zones separated by a melting zone exist; the parent water for the frazil ice is meltwater from congelation ice which appears in the upstream zone.